Analysis of the Traditional and Credit Module System of Training in Higher Education (Information Horizons: American Journal of Library and Information Science Innovation (2993-2777), 2024)
This article analyzes the differences between traditional teaching methods and the credit-module system (CMS) in the higher education system. It is important to consider the differences in the effectiveness of the teaching process, student success in studies, and teaching methodologies between the traditional education system and the credit-module system. In the traditional system, classes are mainly conducted by teachers, in which education develops in a specific direction, but the credit-module system gives students greater freedom, encouraging them to self-manage and independent learning. The article analyzes the advantages and disadvantages of both systems, as well as the factors that affect them in higher education. As a result, it is concluded that the credit-module system can develop as a more effective and positive teaching method in higher education.